The Analysis of the Difficulty in Learning Economics Subject Experienced By Students of Favored State Senior High Schools in City of Malang - Inayati, R; Handayani, S; Kustiandi, J; Haryono, A; Wahyono, H; ., Sapir (KnE Social Sciences, 2018)
Education need to have the ability to improve students’ potentials, namely religion spiritual power, self-management, personality, intelligence, virtuous morals, as well as skills needed by learners and society. Teachers carry an important role to resolve problems related to learning difficulties. The result of the research that was done through interview shows that the types of learning difficulties found in students of favored state senior high schools in the City of Malang are the lack of understanding in receiving information and concept understanding problem. Hence, the solution suggested to solve the problems are: collecting materials taken from compulsory economics textbook and electronic books; asking the teacher regarding the materials that are not yet fully understood; increasing the frequency of exercises in LKS (School’s Exercise Book), or other sources; making summaries, schemes, and notes to ease the comprehension of economics materials’ basic concept; and scheduling studying time outside the school, and at home as well as providing more studying media at home. Keywords: Learning difficulty, economics subject, learning outcome